2005
DOI: 10.1093/ndt/gfh691
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in renal transplant recipients on various immunosuppressive regimens

Abstract: Immunosuppression with TAC or MMF is associated with the development of TB earlier in the post-tx period and in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 16 publications
1
54
1
1
Order By: Relevance
“…The high incidence of TB in kidney transplant recipients is associated with the use of immunosuppressants, such patients already being immunocompromised by chronic renal failure and uremia. (24,25) Among immunocompromised patients, the most common radiological pattern is primary TB, with adenopathy, consolidation, and pleural effusion. (26) In case studies of different types of transplantation, TB is described in its disseminated, extrapulmonary, or miliary form in approximately 45% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of TB in kidney transplant recipients is associated with the use of immunosuppressants, such patients already being immunocompromised by chronic renal failure and uremia. (24,25) Among immunocompromised patients, the most common radiological pattern is primary TB, with adenopathy, consolidation, and pleural effusion. (26) In case studies of different types of transplantation, TB is described in its disseminated, extrapulmonary, or miliary form in approximately 45% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The TB skin tests and culture are often negative in the transplant population. 14,15 As shown in our patient, traditional tests such as Ziehl-Neelsen staining and culture of sputum specimens for revealing Mycobacterium tuberculosis were negative. Therefore, multiple tissue specimens obtained from lymph nodes, bone marrow specimens, liver, kidney, and pleural and peritoneal samples, according to the clinical context, may be necessary.…”
Section: Discussionmentioning
confidence: 61%
“…17 Interferon-gamma detection is a diagnostic test developed recently to improve sensitivity, which allows a rapid TB diagnosis, particularly in patients with culture-negative TB. 14 However, it should not be used initially for diagnosis of active TB.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In a study by Atasever et al, 14 it was reported that immunosuppressive regime including TAC and MMF was associated with the development of TB earlier in the post-transplantation period. Considering that our patient did not have other confounding risk factors such as diabetes, chronic liver disease, low socioeconomic status, and other coexisting opportunistic infection, this may be the major risk factor for predisposition to TB in our case.…”
Section: Discussionmentioning
confidence: 98%